Asian Agriculture, Waste Management, and Sustainable Development Goals - Marzieh Alidoust (Journal of Biotropical Research and Nature Technology, 2025)
This article summarizes the vibrant world of waste management in Asia and its important role in the achievement of sustainable development goals (SDGs). The continent alone has more than 4.5 billion people and produces the greatest amount of waste globally more than 800 million tonnes a year with an estimated increase to 1.8 billion tonnes by 2025 for only urban cities. This is largely attributed to material consumption levels that are high and economic growth as well as urbanization. Third-world countries normally experience infrastructural inadequacies that significantly affect the supply chain of recycling and waste management. Developed countries, however, have recorded outstanding success through investments in technologically developed solutions, effective regulatory frameworks, and waste reduction and recycling schemes. These have compelled them to embrace the 3Rs (reduce, reuse, recycle) and extended producer responsibility (EPR) programs. Waste management in Asia is closely linked with the SDGs, namely, Goal 11 (Sustainable Cities and Communities) and Goal 12 (Responsible Consumption and Production). Effective waste management is at the center of mitigating environmental pollution, protecting public health, and promoting sustainable urbanization. While industrialized nations are concentrating on minimizing waste and advanced treatment technologies, developing nations are leaning toward holistic and decentralized management systems. This review encompasses a number of themes, such as innovations and advancements in waste management, agricultural animal husbandry and waste management, the agriculture products and food industry, waste management strategies and SDG integration in Asian countries, and policy frameworks, technology advances, and institutional arrangements. Asia's waste management sector is currently confronted by a pivotal transformation characterized by enormous disparities between developed and developing nations. Success with sustainable development goals (SDGs) requires the adoption of integrated, inclusive, and innovative approaches reconciling the technical, social, and economic dimensions of waste management processes.